Engaging Resistance: A Poetic Hermeneutical Phenomenology of Mothering - Gringle, Meredith R. (Art/Research International, 2023)
In this article, I discuss the ways that contending with my own resistance around being a mother while researching mothers/mothering, inspired and shaped a study on maternal self-care. Using Judith Butler’s Gender Trouble (2006) as a beginning guide, I discuss how I developed a poetic hermeneutical phenomenology, which emerged as a way out of my resistance and into a deeper relationship with the texts and substance of my project. The purpose of the article is not to present findings; instead, I express my personal and theoretical rationale for the study, offer up my methodology, and provide examples of the poetic performances that steered my analyses. I also reflect upon the ways that I became folded within this project and how my own positionalities affected, and were affected by, engaging in this work. Lastly, I issue a call for qualitative researchers to make explicit our connections to our research, and to interrogate how these connections relate to our goals and gazes.